Learning Management During the Covid-19 Improves the Quality of Learning In MIN Medan - Aswaruddin; Maulidayani (EDUTEC : Journal of Education And Technology, 2021)
This study aims to discuss how learning management improves learning quality during the covid-19 pandemic, the implementation of this study using qualitative descriptive method. The results of this research are steps that can be done by teachers min Medan in improving the quality of learning is by applying learning management patterns. Implementation of educational programs that are good in learning, management is an important part, the implementation of learning management conducted by teachers MIN Medan includes activities (1) Planning learning objectives, (2) Organizing learning by using varied learning resources that aim to make it easier to achieve learning objectives, (3) implementing teacher leadership in the way teachers in learning must always motivate students, by encouraging students in learning activities, and teachers should give attention to students, (4) evaluate learning to know the extent of student development and to know if learning objectives have been optimally achieved, and to know if student constraints in achieving learning objectives. Teacher learning management MIN Medan is a teacher's activity in managing students' learning situations through online learning. In the management of this learning is certainly asked the teacher's expertise and the wisdom of the teacher so that the rhythm of the task given does not burden the students.